2001
DOI: 10.1046/j.1365-2745.2001.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and stage structure in a haploid‐diploid red seaweed, Gracilaria gracilis

Abstract: Summary 1Many red seaweeds are characterized by a haploid-diploid life cycle in which populations consist of dioecious haploid (gametophyte) and diploid (tetrasporophyte) individuals as well as an additional diploid zygote-derived sporangium (carposporophyte) stage. A demographic analysis of Gracilaria gracilis populations was carried out to explore and evaluate the population dynamics and stage structure of a typical haploid-diploid red seaweed. 2 Four G. gracilis populations were studied at two sites on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 56 publications
(110 reference statements)
6
86
0
Order By: Relevance
“…In addition, although differential selection between haploids (males) and diploids (females) has been detected in haplodiploid insects (Pamilo, 1993;Parker and Hedrick, 2000), we did not observe any significant differences in haploid and diploid within-population allele frequencies, suggesting the absence of strong differential selection at our microsatellite, or closely linked, loci. Second, migrationdrift disequilibrium is the most plausible explanation in agreement with our results: since pairwise genetic differentiation between pools was not correlated between the two ploidy levels (Table 5), there may be a lag between migration and (local) breeding due to the long generation times in G. gracilis (420 years, Engel et al, 2001). Finally, in the case of migration-drift disequilibrium, differential migration rates of haploid and diploid spores could account for the higher haploid y y ST values.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, although differential selection between haploids (males) and diploids (females) has been detected in haplodiploid insects (Pamilo, 1993;Parker and Hedrick, 2000), we did not observe any significant differences in haploid and diploid within-population allele frequencies, suggesting the absence of strong differential selection at our microsatellite, or closely linked, loci. Second, migrationdrift disequilibrium is the most plausible explanation in agreement with our results: since pairwise genetic differentiation between pools was not correlated between the two ploidy levels (Table 5), there may be a lag between migration and (local) breeding due to the long generation times in G. gracilis (420 years, Engel et al, 2001). Finally, in the case of migration-drift disequilibrium, differential migration rates of haploid and diploid spores could account for the higher haploid y y ST values.…”
Section: Discussionsupporting
confidence: 86%
“…However, a demographic study of Aud1, Aud2, GN2 and GN3 revealed similar population dynamics in all the pools (Engel et al, 2001). In the absence of differences in survival, fecundity or extinction probabilities and even habitat quality, biased spore dispersal may generate directional gene flow (cf.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…More opportunistic fucoids like the invasive Sargassum muticum, which displays a very large reproductive allocation, seem to rely on the same strategy, irrespective of the state of invasion (Engelen and Santos 2009). Also, the red seaweed Gracilaria gracilis was characterized by high survival and low recruitment rates, consistent with an estimated longevity of 42 years (Engel et al 2001). In contrast, short-lived ephemeral species are predicted to have a very high reproductive effort and associated costs as they do not have to balance costs with future vital rates.…”
Section: Demographic Modelsmentioning
confidence: 83%
“…However, few studies combine field surveys with demographic studies to determine the relative effects of mortality and fecundity on population structure (but see Engel et al 2001).…”
Section: Introductionmentioning
confidence: 99%